The uterine and vascular actions of estetrol delineate a distinctive profile of estrogen receptor α modulation, uncoupling nuclear and membrane activation. Issue 10 (11th September 2014) - Abot, Anne; Fontaine, Coralie; Buscato, Mélissa; Solinhac, Romain; Flouriot, Gilles; Fabre, Aurélie; Drougard, Anne; Rajan, Shyamala; Laine, Muriel; Milon, Alain; Muller, Isabelle; Henrion, Daniel; et al.
Abstract Estetrol (E4) is a natural estrogen with a long half‐life produced only by the human fetal liver during pregnancy. The crystal structures of the estrogen receptor α (ERα) ligand‐binding domain bound to 17β‐estradiol (E2) and E4 are very similar, as well as their capacity to activate the two activation functions AF‐1 and AF‐2 and to recruit the coactivator SRC3. In vivo administration of high doses of E4 stimulated uterine gene expression, epithelial proliferation, and prevented atheroma, three recognized nuclear ERα actions. However, E4 failed to promote endothelial NO synthase activation and acceleration of endothelial healing, two processes clearly dependent on membrane‐initiated steroid signaling (MISS). Furthermore, E4 antagonized E2 MISS‐dependent effects in endothelium but also in MCF‐7 breast cancer cell line. This profile of ERα activation by E4, uncoupling nuclear and membrane activation, characterizes E4 as a selective ER modulator which could have medical applications that should now be considered further.